Imprint of Holocene Climate Variability on Cold‐Water Coral Reef Growth at the SW Rockall Trough Margin, NE Atlantic. (11th August 2018) - Bonneau, Lucile; Colin, Christophe; Pons‐Branchu, Edwige; Mienis, Furu; Tisnérat‐Laborde, Nadine; Blamart, Dominique; Elliot, Mary; Collart, Tim; Frank, Norbert; Foliot, Lorna; Douville, Eric
Abstract: U‐Th ages and temperatures derived from Li/Mg have been measured on coral fragments of Lophelia pertusa and Madrepora oculata collected from two sediment cores, which were taken from cold‐water coral (CWC) mounds at 700–790m water depth at the SW Rockall Trough margin. Our data, combined with previous published data, have allowed us to first estimate the occurrence of CWC at the SW Rockall Trough margin during the Holocene and, second, to better constrain the environmental conditions driving variability in CWC growth. CWC abundance is marked by a pronounced increase in the mid‐Holocene (∼6 ka) and is modulated by millennial‐scale variability throughout the late‐Holocene. The mid‐Holocene proliferation of CWC coincides with lowest IRD abundances and a major reorganization of the circulation at thermocline depth in the Rockall Trough, marked by the progressive replacement of the fresh‐cold Sub‐Arctic Intermediate Water (SAIW) by the saltier and nutrient‐rich Eastern North Atlantic Water (ENAW). This event must have established a modern‐like winter mixed layer and thermocline structure, generating suitable conditions for enhanced surface productivity, downslope transport of food particles, bottom current acceleration at mound depth and thus CWC growth. Several short time intervals of decreased CWC occurrences closely match prominent increases in North Atlantic drift ice and storminess in Northern Europe. We, therefore, propose that high detrital supply and/or changes in the vertical density gradient associated with millennial‐scale ice‐rafted detritus (IRD) events are the likely controlling factors for CWC growth and subsequent mound formation on the SW Rockall Trough margin. Key Points: First detailed record of cold‐water corals occurrence at the SW Rockall Trough margin during the Holocene Evidence of a mid‐Holocene increase in the cold‐water corals occurrence associated to major reorganization of the hydrology Strong evidence of millennial climatic control on the CWC growth in the SW Rockall Trough during the late‐Holocene